Implementation of carbon tax in Indonesia: Literature Review on Its potential and impact - Apri Dwi Astuti; Rinti Dwijayantie; Tri Nurul Khomidah; Sigit Munandar; Diva Ayu (Proceeding International Conference on Accounting and Finance, 2026)
Carbon tax is a fiscal instrument designed to reduce greenhouse gas emissions and support the transition to a green economy. Although carbon tax has the potential to reduce emissions, its implementation still faces a number of challenges. This study aims to analyze the potential and impact of carbon tax implementation in Indonesia through a literature review approach. Carbon tax is a fiscal instrument designed to reduce greenhouse gas emissions while supporting the transition to a green economy. The research method used a literature review by examining indexed scientific articles from 2019 to 2025 that are relevant to the topic of the potential and impact of carbon tax. The results of the study show that carbon tax in Indonesia has great potential to increase state revenue, promote energy efficiency, accelerate investment in renewable energy, and change the behavior of the community and business actors towards the use of low-emission technologies. However, carbon tax also has complex impacts, including increased production costs, decreased competitiveness of certain industries, a regressive burden on low-income households, and the potential for a slowdown in the agricultural sector. In conclusion, carbon tax can be an effective policy instrument in climate change mitigation efforts if it is designed with balanced consideration of economic, social, and environmental aspects. To ensure successful implementation, clear supporting regulations, compensation mechanisms for vulnerable groups, and integration with other green fiscal policies are required.